A seawater RO desalination process driven by dynamic pressure of high-speed seawater droplets. (7th January 2021) - Xiang, Yi; Lu, Hui; Ma, Qingfen; Hao, Mengnan
Seawater reverse osmosis (RO) desalination requires driving pressure of 5 8 MPa which is usually offered by the high-pressure pump, the standard device employed in the commercial application, accompanied by a series of problems. To replace the high-pressure pump, a seawater RO desalination technique driven by the dynamic pressure of high-speed seawater droplets is proposed. By theoretical calculation and computational fluid dynamic (CFD) simulation, the required operating conditions for the acquisition of effective impacting seawater droplets were investigated. The results showed that the velocity of the seawater droplets should exceed 70 m/s to achieve the driving pressure of 5 MPa, and simultaneously the air flow velocity should exceed 70 m/s to act as the accelerating medium. The proper size of the accelerated droplets at different air flow velocity within the range of 70 100 m/s was determined not only considering the final velocity of the droplets but also their gravitational settling limitation. In addition, five structures of the RO membrane module were designed and tested, in which the ring-shaped and semicircle-shaped structure exhibited good performance with droplet trap rate greater than 90%. Furthermore, the energy balance of the whole system was analysed, and some constructive suggestions are provided to reduce the energy consumption.